Analysis of Key Factors of Hotel Facilities Competitive Fitness - Natalia E. Goryushkina, Yuri M. Avdeev, Irina F. Vetrova, Alexandr N. Dunets, Taisiya F. Ryabova, Nadezhda Yu. Sukhina (International Journal of Advanced Science and Technology, 2020)
The author has determined factors of hospitality industry’s facilities competitive fitness. Also, the fact that competitiveness is one of the key stimulus of making progress in the hotel services market has been underlined. A hotel facility competitive fitness depends on the number of factors which can be considered as aspects (integral parts) of competitive fitness. The key aspects of hotel facilities competitiveness have been determined, an analysis of the selected hotels based on their competitive factors has been made and the hotels competitive fitness has been evaluated using modified Delphi approach. Solving of the research task has been based on objectivity and specifity principles.